The study of the elements of corporate culture of modern medical organization in the conditions of the Russian market of medical services - E. V. Shamalova; M. I. Glukchova; V. G. Vaskaeva (Путеводитель предпринимателя, 2020)
The article presents the analysis of the main elements of corporate culture of foreign medical organizations, which for many years successfully working in the Russian market, the EU standards in the complex Russian reality. Investigated: mission, strategy and basic principles of corporate culture, core values, shared and declared the most reputable members of the organization. Assessed values of corporate culture by the method of G. Hofstede identified values, which are shared by the majority of the center staff. The proposed adjustment values, which will allow to reconcile the aspirations and goals of top management and employees of Junior and middle medical personnel.